Пространственная реорганизация архитектуры хромосом в генеративной системе является механизмом сальтационного видообразования - Стегний, В.Н. (Фактори експериментальної еволюції організмів, 2016)
Speciation can not be regarded as a long-term process of gradual adjustment ancestral species gene pool. The concept
of «gene pool» entirely relates to the polymorphic part of the genome, while it is clear that speciation events affect
primarily monomorphic (invariant) and part of this is accompanied by irreversible reorganization of its regulatory
system. Saltational speciation, based on the emergence of spatial reorganization of the architecture of the chromosomes
in the generative system most likely to occur in a critical influence of abiotic and biotic factors, which are defined as
environmental conditions periphery.
Keywords: speciation, reorganization, architecture, chromosome.